Critical pedagogy: an emancipatory alternative in the neoliberal context (Revista Innova Educación, 2021)
At present, neoliberalism has a predominance over society, generating a crisis of all kinds. The objective of this work was to analyze education in the neoliberal context and study the alternative of critical pedagogy as a way out of the current educational crisis. For the analysis, the qualitative method was used with a documentary-type design, for which a review of scientific literature related to education, neoliberalism and critical pedagogy was made. The review of the scientific literature allowed us to understand the political and educational crisis of the neoliberal model, likewise, it allowed us to know a proposal called critical pedagogy that makes it possible to emancipate the academic, cultural, ecological and social context, fostering critical thinking and exercising citizenship.
Keywords: education; state; commodification; neoliberalism; critical pedagogy